Agriculture in the Fatimid Era 296-567 A.H. / 909-1171 A.D. - Ali Faisal Abdul Nabi Al Ameri ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Fatimids gave agriculture the necessary attention, because it is an important economic feature in people’s lives. They were interested in cultivating all kinds of agricultural crops, whether winter or summer, and purified rivers and canals that had been subjected to a lot of siltation due to the accumulated sediments of the Nile River.   Egypt was known for many types of agricultural lands, including: is the best kind of land , the bronite is of lower guality than albak, the cultivated dirt is the land that the farrmer could not completely purify , and others. And the state stood firmly to curb the economic crises that passed through Egypt, such as the drop in the levels of the Nile River and the resulting famines and cases of high prices. They enacted important laws to limit the slaughter of cows as long as healthy ones were able to plow the land, and made the collection of abscesses a priority of its financial organizations, organized in a way Accurate in a way that preserves the rights of farmers and secures sufficient money for the state. The state preserves the rights of farmers and limits the influence of land acceptors, listens to their complaints and works to address their problems.In the era of the Fatimids, the system of commitment or land guarantee appeared, and in addition to this system appeared (the sharing system), which means dividing the land into one-third, two-thirds or one-half in light of the distance and proximity of the agricultural lands to the markets, as well as the method of irrigating the land, or another system which is (the sharecropping system), However, the last two systems have very limited work.DOI /10.54633/2333-021-042-023